2022
DOI: 10.1192/j.eurpsy.2022.2331
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for COVID-19 is associated with a higher risk of subsequent hospitalization for psychiatric disorders: A French nationwide longitudinal study comparing hospitalizations for COVID-19 and for other reasons

Abstract: Hospitalization for COVID-19 is associated with a higher risk of subsequent hospitalization for psychiatric 1 disorders: a French nationwide longitudinal study comparing hospitalizations for COVID-19 and for other 2 reasons 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…As such, we plan to extend our investigation outside of Israel in the future. Second, it is also important to note that global and local circumstances such as political tensions and the COVID-19 pandemic could have influenced the hospitalization patterns of the studied population (Decio et al, 2022;Yaniv-Rosenfeld et al, 2023a). These events are hard to control in our context but we believe that these merit a dedicated future investigation.…”
Section: Discussionmentioning
confidence: 91%
“…As such, we plan to extend our investigation outside of Israel in the future. Second, it is also important to note that global and local circumstances such as political tensions and the COVID-19 pandemic could have influenced the hospitalization patterns of the studied population (Decio et al, 2022;Yaniv-Rosenfeld et al, 2023a). These events are hard to control in our context but we believe that these merit a dedicated future investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Following these studies, we analyzed the whole French Metropolitan general population [33] and found a slightly -but signi cantly -higher rate of hospitalization for psychiatric disorders in the 12 months following hospitalization for COVID-19 in comparison to hospitalization for another reason (unadjusted odds-ratio (OR) = 1.20, 95% con dence interval (95% CI) [1.18-1.23]). The rate was also higher when looking speci cally at psychotic disorders (OR = 1.11, 95% CI [1.05-1.19]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we could analyze if the psychotic disorder was the main reason of the hospitalization ("main" diagnosis) or if it was considered a comorbid condition of the main reason of the hospitalization ("associated" diagnosis). In this last case, we could investigate how COVID-19 could increase global health vulnerability among subjects with psychotic disorders (by analyzing different types of hospitalization, in psychiatric and non-psychiatric wards).To act on these research possibilities, using the same dataset employed for our study on psychiatric disorders in the whole French Metropolitan general population [33], the present longitudinal study aimed to determine the risk of hospitalization for different non-affective psychotic disorders in the 12 months following discharge from hospital for COVID-19 during the rst wave of pandemic, in comparison to discharge from hospital for another reason. Different types of psychotic disorders were described, as well as acute and chronic disorders.…”
mentioning
confidence: 99%
See 2 more Smart Citations